The role of serum beta-human chorionic gonadotropin as a predictor for pregnancy induced hypertension in 12-20 weeks of pregnancy - Singh, Shakun; Gupta, Swati; Chaudhary, Rachna; Dhama, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy-induced hypertension occurs in approximately 3 to 5% of pregnancies and is still a major cause of both fetal and maternal morbidity and mortality worldwide. Pre-eclampsia is risk factor for stillbirth, intrauterine growth restriction (IUGR), low birth weight (LBW), preterm delivery, respiratory distress syndrome, and admission to neonatal intensive care unit. Overall, the incidence of preeclampsia ranges from 5 to 15% in India. This study conducted to assess the predictive value of raised beta-human chorionic gonadotropin (β-hCG) levels in development of pregnancy-induced hypertension in antenatal women and follow up the risk patients and reduce both maternal and perinatal morbidity and mortality. Methods: The present study was conducted in the department of obstetrics and gynaecology, L.L.R.M Medical College and associated SVBP Hospital, Meerut during the period of January 2021 to December 2021 on 400 antenatal women with 12 to 20 weeks of gestation. Estimation of serum beta hCG level was done by enzyme linked fluorescence immunoassay. The cases were followed up in antenatal clinics, 4 weekly till 28 weeks, fortnightly up to 34 weeks and thereafter weekly till delivery for the development of PIH. Results: From the study it was found that women with elevated beta hCG values in 12-20 weeks were at increased risk of developing PIH. The sensitivity of β-hCG for development of PIH was found to be 90%. It was found that specificity, positive predictive value (PPV), negative predictive value (NPV) of β-hCG for development of PIH was 82%, 41.7%, 98.3% respectively. However, p value of β-hCG for development of PIH is 0.001 which is highly significant. Conclusions: From this study we found that that measuring second trimester serum beta-hCG levels is a good predictor of pregnancy induced hypertension and showed association with elevated levels of beta hCG with development and severity of PIH, but sensitivity and positive predictive value of beta hCG are low in this study to be useful for mass screening marker on its own.